Evaluating The Policy Impact Of Regional Public Service Agency On Vocational Education Quality In East Java - Mufarrihul Hazin; Muhamad Turhan Yani; Suyatno Ladiqi; Nur Wedia Devi Rahmawati (Sakura Digital Nusantara, 2026)
Background: Vocational education is expected to produce graduates who are ready for the labor market; however, gaps between school learning and industry demands remain a persistent issue. Policy interventions such as BLUD have been introduced to enhance institutional flexibility, yet their impact on student outcomes is not fully understood. Objective: This study aims to examine the effect of BLUD policy implementation on students’ job readiness by incorporating key educational process variables, including learning facilities, teaching effectiveness, practical activities, and potential development. Methods: A quantitative approach with a causal-explanatory design was employed. Data were collected from 583 students from 21 vocational school. The model includes six latent variables with 19 indicators and was analyzed using PLS-SEM. Findings: The results show that BLUD policy has strong effects on educational processes, particularly on learning facilities (β = 0.728), teaching effectiveness (β = 0.662), practical activities (β = 0.636), and potential development (β = 0.760). The model demonstrates high explanatory power (R² = 0.725). Research Implications: These findings highlight the need to shift policy focus from infrastructure provision to strengthening experiential learning, industry-based practice, and student development programs. Optimizing BLUD flexibility should prioritize practice-based learning systems to enhance employability outcomes. Originality: This study provides a novel perspective by demonstrating that vocational education effectiveness is driven more by process-based factors than structural inputs, challenging infrastructure-centered policy approaches.